ANALISIS PENGENDALIAN INTERNAL KAS DAN PIUTANG TERHADAP EFEKTIVITAS ARUS KAS PADA PT. SINAR LESTARI UTAMA - Regina Jaya (Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Basically, the main goal of the company is to maximize profits, maximize company growth and ensure company survival. The research method used in this research is a descriptive method, namely a research method by studying the methods used to describe or describe a collection of data or the results of observations that have been made. The aim is to provide an overview of the data or object being studied so that the data presented can be easily understood by other people who read it. The research results show that there is an organizational structure and employee job descriptions that reflect the duties and responsibilities of each employee from each department in the company, and encourage employees to comply with existing regulations, there is also a division of functions related to authority, monitoring, recording and Cash storage includes procedures related to company cash and the implementation of monitoring cash receipt and distribution reports received by the Finance Department. The company implements 4 credit limit conditions such as Capacity, Collateral, Character and Condition, so that it is sufficient to create internal control of cash and credit within PT. Sinar Lestari Utama is quite effective and efficient which intentionally or unintentionally provides effectiveness in the cash flow report